Description of new members of the family Cylindroleberididae (Ostracoda: Cylindroleberidoidea) from the Southern Ocean - Chavtur, Vladimir G.; Keyser, Dietmar (Zootaxa, 2016)
We report new ostracod data (Family Cylindroleberididae) based on material collected during the German Expeditions onboard the research vessel “Polarstern” from bathyal and abyssal zones (sampling depth range from 1030 to 3963 m) in the Weddell and Scotia Seas and Drake Passage in 2002 and 2005. Four species belonging to four genera were identified in these collections. A new species, Synasterope pseudomystax, is illustrated and described. A first occurrence of an adult female is registered for Archasterope weddellensis (Kornicker, 1975). Additional description for Parasterope cf. styx Kornicker, 1975 is given. Description of Bathyleberis grossmani Kornicker, 1975 is supplemented with new data on the distribution. Additionally, keys for all species known for Antarctic waters are included.